Pedagogical Factors for the Development of Students' Professional Competence in the Educational Process: A Study in Uzbekistan - Akmoljon, Ibroximova Shaxlo (WaPFi (Wahana Pendidikan Fisika), 2025)
Professional competence has consistently been a primary focus for higher education systems aiming to equip graduates for the demands of the contemporary job market. This study examines the pedagogical factors affecting the enhancement of teacher students' professional competence in Uzbekistan, based on a comprehensive literature review. The review, utilizing the PRISMA framework, emphasized five critical components that characterize competence-based education: active learning methodologies, work-integrated learning, assessment and feedback mechanisms, teacher professional development, and institutional support systems. The research aimed to demonstrate that aligning the curriculum with industry objectives, incorporating real-world learning experiences, employing formative assessment methods, investing in teacher training, and enhancing institutional capacity are essential for attaining professional competence. Policy suggestions underscore cohesive strategies for curriculum reform, faculty enhancement, and employer engagement. The paper recommends conducting longitudinal studies to evaluate the effects of educational interventions on graduates' employment performance and employability.